2012
DOI: 10.5014/ajot.2012.004234
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive Processing Difficulties Among Children With Autism Spectrum Disorders and Developmental Disabilities

Abstract: Objective Sensory processing difficulties among children with autism spectrum disorders (ASD) have been extensively documented. However, less is known about this population's ability to process proprioceptive information. Method We used the Comprehensive Observations of Proprioception (COP; Blanche, Bodison, Chang, & Reinoso, in press) to describe the proprioceptive difficulties experienced by children with ASD. A sample of 32 children with ASD, 26 children with developmental disabilities excluding ASD, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 20 publications
2
38
0
2
Order By: Relevance
“…Contrary to a stable surface, ML oscillations predominated under all conditions on the unstable surface (Table 2). One possible explanation for this event may be that the alteration of the proprioceptive system is responsible for the adjustment of the activation of the musculature of the trunk, thus causing instability in the ML direction (Blanche et al, 2012;Fournier et al, 2010b;Hansson et al, 2010). Another possible justification might be related to balance control in the ML direction, mainly occurring due to weakness at the hip and trunk areas.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Contrary to a stable surface, ML oscillations predominated under all conditions on the unstable surface (Table 2). One possible explanation for this event may be that the alteration of the proprioceptive system is responsible for the adjustment of the activation of the musculature of the trunk, thus causing instability in the ML direction (Blanche et al, 2012;Fournier et al, 2010b;Hansson et al, 2010). Another possible justification might be related to balance control in the ML direction, mainly occurring due to weakness at the hip and trunk areas.…”
Section: Discussionmentioning
confidence: 99%
“…These results lead us to believe that proprioceptive input in children with autism could interfere with the ability of this system to send the correct information to maintain proper postural stability. (Blanche et al, 2012;Fournier et al, 2010b;Hansson et al, 2010;Shumway-Cook & Woollacott, 2001b). Contrary to a stable surface, ML oscillations predominated under all conditions on the unstable surface (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, participation in sports tend to require motor control and several studies have reported on the motor control difficulties in children with ASD, including how proprioceptive difficulties among children with ASD may contribute to decreased motor planning and to disruptive behaviors that negatively affect their participation in daily tasks. 19 Thus, participation in STEM based gamified activities can serve as an alternative opportunity to develop collaborative and social communication skills. The AR Drone lab affords students with ASD a chance to participate in an activity based on their interest while also providing an opportunity to develop the critical social skills for future success.…”
Section: Motivationmentioning
confidence: 99%